2012
DOI: 10.1093/rpd/ncs125
|View full text |Cite
|
Sign up to set email alerts
|

Occupational radiation exposure in Tanzania (1996-2010): status and trends

Abstract: Data on occupational radiation exposure using the thermoluminescence dosimetry methodology in Tanzania for the years 1996-2010 are analysed and discussed. The results of the analysis indicate that over 80 % of the total collective dose was from diagnostic radiology. In addition, <1 % of workers received annual individual doses above 5 mSv, and there were no doses that exceeded the recommended limit of 20 mSv y(-1), except for one incidence in non-destructive testing. Furthermore, the trends in occupational exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Moreover, exposure monitoring of occupational workers also provides information regarding the capability and effectiveness of the radiation protection program. In addition, individual monitoring program also aims to reveal compliance with maximum permissible dose limit as required by the national regulations and international recommendations and standards [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, exposure monitoring of occupational workers also provides information regarding the capability and effectiveness of the radiation protection program. In addition, individual monitoring program also aims to reveal compliance with maximum permissible dose limit as required by the national regulations and international recommendations and standards [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, a large cohort of studies focusing on the assessment of occupational exposed medical worker has been reported from around the globe, including Pakistan [6][7][8][9][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. These studies, in particular those reported from Pakistan, are scattered, discuss/ focus on different dosimetry indices and non-overlapping study periods, all confounding a meaningful analysis and comparison.…”
Section: Introductionmentioning
confidence: 99%